Biomechanical Analysis of Posterior Lumbar Interbody Fusion Cages with Various Infill Pattern Designs - Mior Idris, Wan Nur Arifah; Mazlan, Muhammad Hazli (Evolution in Electrical and Electronic Engineering, 2020)
Degenerative disc disease (DDD) is a spinal condition when intervertebral disc that can help to protect the nerves and increase the flexibility of the spine begin to collapse. One of the treatment techniques is Posterior Lumbar Interbody Fusion (PLIF) surgery. However, many unresolvable clinical implications such as cage deformation, mechanical cage failure and stress shielding effects. This project aim to develop various infill pattern of interbody cage design to suit bones’ compatibility’s order to reduce the consequences of PLIF technique by using Finite Element Analysis (FEA). Material used was Polylactic Acid (PLA) and Solidworks software was used to design the interbody cages. The designed interbody cage was implanted between first lumbar (L1) and second lumbar (L2) vertebra which was extracted from CT scan images in 3D Slicer software. The implanted model was analysed in Ansys Workbench Software to determine the structural strength of the designed interbody. The implanted model analysed in terms of Von Mises Stress and Maximum Principal Stress values on the conditions of the motions such as flexion, extension, axial rotation, lateral bending and compression force. From the results, the interbody cage of honeycomb infill pattern is the most reliable biomechanical construct by showing the minimal value of Von Mises Stress and Maximum Principal Stress. In conclusion, the interbody cage with honeycomb infil pattern exhibited higher dimensional accuracy and higher compressive properties than rectilinear infill pattern structures.